Chemical Composition and Antifungal In Vitro and In Silico, Antioxidant, and Anticholinesterase Activities of Extracts and Constituents of Ouratea fieldingiana (DC.) Baill. (7th November 2018) - Nascimento, José Eranildo Teles do; Rodrigues, Ana Livya Moreira; Lisboa, Daniele Silva de; Liberato, Hortência Ribeiro; Falcão, Maria José Cajazeiras; da Silva, Cecília Rocha; Nobre Júnior, Hélio Vitoriano; Braz Filho, Raimundo; Paula Junior, Valdir Ferreira de; Alves, Daniela Ribeiro; de Morais, Selene Maia
Abstract : Ouratea fieldingiana (Gardner) Engl is popularly used for wound healing. This study describes the main chemical compounds present in extracts of O. fieldingiana and evaluates their biological potential by investigating antifungal, antioxidant, and anticholinesterase activities. The action mechanism of main antifungal compound was investigated by molecular docking using the enzyme sterol 14- α demethylase, CYP51, required for ergosterol biosynthesis. The seeds and leaves were extracted with ethanol in a Soxhlet apparatus and by maceration, respectively. Both extracts were subjected to silica gel column chromatography for isolation of main constituents, followed by purification in sephadex. The structures of compounds were established by 1 H and 13 C-NMR spectroscopy and identified by comparison with literature data as amentoflavone and kaempferol 3- O -rutinoside, respectively. The antioxidant activities of the extracts were determined by the DPPH and ABTS free radical inhibition methods. In general, the extracts with the highest antioxidant activity corresponded to those with higher content of phenolic compounds and flavonoids. The ethanol extracts and two isolated compounds presented relevant antifungal activity against several Candida strains. The in silico findings revealed that the compound amentoflavone coupled with the CYP450 protein due to the low energy stabilization (-9.39 kcal/mol), indicating a possible mechanism of action by inhibition of the ergosterol biosynthesis of Candida fungi.